The Role of Job Satisfaction in Mediating the Impact of Work-Life Balance and Employee Engagement on Organizational Commitment - Monata, Deri; Yulihasri, Yulihasri (Dinasti International Journal of Management Science, 2024)
This study investigates the influence of work-life balance, employee engagement, and job satisfaction on organizational commitment among employees. Utilizing a quantitative method with a causal design, data were collected from 191 employees through questionnaires. The results indicate that employee engagement and job satisfaction significantly impact organizational commitment. Employees who are more engaged and satisfied tend to have higher levels of commitment. Additionally, work-life balance was found to positively affect job satisfaction, with a good work-life balance enhancing employee satisfaction. The study also revealed that job satisfaction and employee engagement mediate the effect of work-life balance on organizational commitment. Therefore, a good work-life balance increases job satisfaction and employee engagement, ultimately enhancing organizational commitment. This research contributes to the understanding of the relationships between work-life balance, employee engagement, job satisfaction, and organizational commitment, providing practical guidance for management in creating a supportive work environment to boost employee motivation and commitment.